The Influence of Transformational Leadership on Employee Performance at The Binjai City Inspectorate Office - Pimanta Tarigan, Edy; Farida Ferine, Kiki (PT. Multidisciplinary Press Indonesia, 2024)
The purpose of this research is to determine and analyze the influence of Transformational Leadership on Employee Performance of Binjai City Inspectorate Office Employees. This research was carried out at the Binjai City Inspectorate Office. The type of research is associative quantitative. The sample in this study was 60 employees of the Binjai City Inspectorate Office. The sampling technique in this research uses saturated samples so that the entire population will be a sample of 60 people. The research results show that Transformational Leadership has a significant influence on Employee Performance as shown by the T-Statistic value of 3.037 > 1.670 and the P Value of 0.004 < 0.05. This shows that improvements in Transformational Leadership can improve the Performance of Binjai City Inspectorate Office Employees.